2022
DOI: 10.3389/fphar.2022.947303
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating effect of the biological Zinc nanoparticles in abamectin induced hepato-renal injury in a rat model: Implication of oxidative stress, biochemical markers and COX-2 signaling pathways

Abstract: Extensive use of abamectin (ABM) as an anthelmintic in veterinary systems adversely affects the health and welfare of animals and humans. Zinc nanoparticles (ZnNPs) have therapeutic benefits and ameliorate the effect of environmental pollutants. In this study, we assessed the ameliorative effect of ZnNPs against the sub-lethal toxicity of ABM in rats. Forty healthy rats were randomly selected into four groups (n = 10); the control received normal saline and test rats were treated orally twice weekly with ABM (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 81 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…Also, Expression of COX-2 is associated with inflammation and is released by an array of proinflammatory stimuli [ 99 ]. Interestingly, a diffuse positive cytoplasmic expression of COX-2 illustrates the enormous cytoplasmic immunoreactivity for detecting COX-2 antigen in the livers and kidneys of abamectin-treated rats [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Expression of COX-2 is associated with inflammation and is released by an array of proinflammatory stimuli [ 99 ]. Interestingly, a diffuse positive cytoplasmic expression of COX-2 illustrates the enormous cytoplasmic immunoreactivity for detecting COX-2 antigen in the livers and kidneys of abamectin-treated rats [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be because cinnamaldehyde can operate as a free radical scavenger, antioxidant, and anti-inflammatory agent [ 101 ]. Attaining notable downregulation of COX-2 enzyme expression during oxidative stress could be a critical strategy in regulating liver and kidney destruction [ 100 ]. Moreover, trans-cinnamaldehyde treatment uncovered anti-inflammatory actions by downregulating COX-2 expressions compared with methotrexate alone [ 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous investigation (Othman et al, 2019;Abdelnour et al, 2020), we isolated and identified the PRG from Serratia marcescens and lyophilized then the PRG was supplemented into diets conferring to the experiment protocol. For the zinc nanoparticles (ZnNPs), the Lactobacillus plantarum VITES07 was used for the biogenic ZnNPs, as described in our previous work (Aioub et al, 2022). Then, the TEM recognized the ZnNPs (transmission electron microscope, type JEOL-JEM 2100).…”
Section: Materials Preparationmentioning
confidence: 99%
“…14 Aioub et al demonstrated that alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase levels were increased after AVM stimulation in rats. 15 Furthermore, when lactating animals were exposed to AVM, a notable reduction in the body weight of the female subjects was observed. Simultaneously, the function of hepatic antioxidant enzymes experienced a decline, while the activity of lactate dehydrogenase (LDH) showed an escalation in female offspring.…”
Section: Introductionmentioning
confidence: 98%
“…Toxicological studies of AVM have shown that AVM intoxication usually causes an increase in liver–body ratio, hepatocyte edema with nuclear translocation . Aioub et al demonstrated that alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase levels were increased after AVM stimulation in rats . Furthermore, when lactating animals were exposed to AVM, a notable reduction in the body weight of the female subjects was observed.…”
Section: Introductionmentioning
confidence: 99%